KAJIAN KARYA SASTRA PERUNDUNGAN VERBAL DALAM KOMIK - Sultan Daffa Rahadian; Nungki Heriyati (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
The analysis attempts to examine teenagers' behaviour towards poor physical appearance people as reflected in a comic entitled â€œNever Understandâ€. They tend to bully those people verbally. This article uses Library research methods to seek out the representation of bullying, especially verbal bullying since they tend to do it than physical one. It also examined the factor and identified whole consequences from bullying. The analysis found that verbal abuse towards the main character, along with the factors that cause the perpetrator to commit bullying, and the aftermath of bullying to the main character. with this due, it simplified that lack of integrity to self, obnoxious surroundings and environment. For this case, it forced teenagers to create such nuisance conditions. In addition, to conclude that bullying will harm every individual, especially for people who have deficiencies.